Eccrine Nevus in the Forearm of a 16-Year-Old Presenting as Unilateral Hyperhidrosis: A Clinicopathological Correlation Paradigm - Alejandro Martin-Gorgojo; Ignacio Sanchez-Carpintero; Ricardo Ruiz-Rodriguez; Ana-Belen E (MDPI AG, 2021)
A case of a purely eccrine nevus in an adolescent patient presenting with focal hyperhidrosis on an area comprising the left forearm and the dorsal aspect of the left hand is described. No clinically evident lesions were identifiable. Dermatopathologic findings were subtle, showing only a slight increase in the number of eccrine glands. Clinicopathological correlation was paramount to achieve the diagnosis.